Determination of dielectric properties and predictive modeling for designing radio-frequency heating of ground beef - Purohit, Anuj; Kumari, Ankanksha; Roy, Anupam; Mohan, Anand (Frontiers in Food Science and Technology, 2022)
Dielectric properties of ground beef as affected by the variation of fat content (73/27, 80/20, and 85/15 lean/fat) and temperature (0 to 90°C) to were determined using a parallel plate LCR meter and liquid test fixture at the radiofrequency (RF) of 27.12 MHz. The values of dielectric constant and dielectric loss factor significantly increased with temperature (p<0.05) whereas the values of penetration depth dp decreased with temperature (p<0.05) up to the respective points of local extrema. Values of both ε' and ε'' were significantly lower (p<0.05) for the leaner blend 85/15 and conversely, penetration depth was significantly higher (p<0.05) for the leaner blend. As temperature increased beyond the point of maximum for ε' and ε'' and point of minimum for dp, there was no significant difference in the dielectric properties between the different lean/fat blends. Predictive equations of second order in temperature and fat content were developed for the dielectric properties which explained 74, 93, and 98% variation in ε', ε'', and for dp respectively, based on R2 values. The dielectric properties and their fitted models can be utilized for designing pilot and mass scale RF processes for heating ground beef.